Bridging the humanitarian-development divide in a protracted crisis: a case study of the use of a central plant to supply oxygen for COVID-19 case management in South Sudan - Olu, Olushayo Oluseun; Freeman, Alex Yao Sokemawu; Waya, Joy Luba Lomole; Guyo, Argata Guracha; Kanu, Benedict; Tukuru, Michael; Maleghemi, Sylvester (Frontiers in Public Health, 2023)
The rising demand for medicinal oxygen due to the COVID-19 pandemic exacerbated an underlying chronic shortage of the commodity in Africa. This situation is particularly dire in protracted crises where insecurity, dysfunctional health facilities, poor infrastructure and prohibitive costs hinder equitable access to the commodity. Against this backdrop, the Ministry of Health of South Sudan, with the guidance of its partners, procured and installed a pressure swing adsorption central oxygen supply plant to address the shortfall. The plant aimed to ensure a more sustainable and technologically appropriate medicinal oxygen supply system for the country and to bridge the humanitarian and development divide, which had always been challenging. This article discusses the key issues, challenges and lessons associated with the procurement and installation of this plant.The major challenges encountered during the procurement and installation of the plant were the time it took to procure and install in the face of urgent needs for medicinal oxygen and its short and long-term sustainability. Lessons learnt include the need for exhaustive and evidence-based considerations in deciding on which source of medicinal oxygen to deploy in protracted crisis settings. The successful installation and operationalization of the plant demonstrated that it is possible to bridge the humanitarian-development divide amidst the complexities of a protracted crisis and an ongoing pandemic. The Ministries of Health, with the support of its partners, should assess and document the impact of this and other similar central oxygen production plants in protracted crisis settings regarding their sustainability, cost, and effectiveness on medicinal oxygen supply. The Ministry of Health of South Sudan should expedite the finalization and operationalization of the longer-term public-private partnership and continue to monitor the quality of oxygen produced by this plant.